Adolescent social media use and mental health in sub-Saharan Africa: a scoping review protocol of current research - Shane A Norris; Witness Mapanga; Rachana Desai; Lauren Stuart; Claire Hart (BMJ Open)
Introduction There is growing public concern and emphasis on the potential negative implications of social media on adolescent mental health and the implementation of social media restrictions, despite limited and mixed evidence that predominantly originates from the Global North. In sub-Saharan Africa (SSA), where adolescent populations are rapidly expanding and adopting technology, research on social media and mental health is limited. This scoping review aims to map and describe the available evidence on social media use and mental health among adolescents in SSA.Methods and analysis This study employs the scoping review methodology from the Joanna Briggs Institute, following a five-stage process: (1) determining the research question, (2) creating a search strategy, (3) defining inclusion criteria, (4) extracting data, (5) conducting analysis, presentation, and (6) consultations. The search strategy will be applied to databases such as PsycINFO, PubMed (Medline and OVID), Web of Science, LILACS, Scopus, Google Scholar, ProQuest Dissertations and PsycINFO Extra, covering both empirical and grey literature. Articles will be independently assessed for eligibility with data extraction and charting performed using a standardised form. Visualisation tools, such as a heatmap for the prevalence of studies in SSA and a network diagram depicting relationships, will be used.Ethics and dissemination Ethics approval was not required for this review. Dissemination will occur through a peer-reviewed journal article, academic presentations and online news media in the form of a commentary which will be publicly available.